Variations in hydrological variables using distributed hydrological model in permafrost environment - Ahmed, Naveed; Wang, Genxu; Booij, Martijn J.; Marhaento, Hero; Pordhan, Foyez Ahmed; Ali, Shahid; Munir, Sarfraz; Hashmi, Muhammad Zia-ur-Rehman (2022)
The Yangtze River Source Region (YaRSR) is located in the third polar region, the most threatened zone by global warming after the Arctic. Permafrost covers eighty percent of the total area of YaRSR, while the rest is seasonally frozen ground. Due to a significant rise in air temperature, degradation of the permafrost could occur. Permafrost coverage in a river basin greatly controls its hydrology. This study focuses on hydrological modeling in this permafrost environment using the Soil and Water Assessment Tool (SWAT). The SWAT model was calibrated (1985–2000) and validated (2001–2015) on a daily time step. The results were also compared on a monthly time scale. An impermeable layer was introduced within the SWAT model to represent the permafrost conditions. The streamflow is strongly dependent on the seasonal variation of precipitation and temperature, and the rising limb of the hydrograph shows the melting of snow, the contribution of soil water, and thawing of permafrost during the spring-summer season. The permafrost layer well restricted the deep percolation of water. During the spring season, streamflow mainly consists of surface runoff because of the frozen soils. Permafrost and frozen ground thawing lead to an increase in the contribution of groundwater flow to streamflow. Ultimately, the frozen ground depletes as the temperature gets close to the freezing point. This study also describes the SWAT model application to better analyze and understand the hydrology of the permafrost/frozen ground with limited data availability. © 2022